Results of Dermal Patch Graft in the Treatment of Peyronie’s Disease - A A Khezri; Shahriyar Zeighami; Darioush Irani (Urology Journal, 2004)
Purpose: To investigate the efficacy of “dermal patch graft” in surgical management of Peyronie’s. Materials and Methods: eighteen of Peyronie’s disease cases, with a mean age of 49 and a history of penile curvature and painful erection were enrolled in this study. Diagnosis was made clinically by plaque palpation. All of them were in the chronic stage of disease with symptom duration of at least 6 months. We also evaluate their potency through Brief Sexual Function Inventory (BSFI) questionnaire before and after the operation, meanwhile the degree of penile curvature was measured with goniometry while artificial erection status was induced. Results: Mean penile curvature, before and after the operation (58 and 5 degrees respectively), showed significant improvement (P < 0.001). The improvement of curvature was irrespective of the plaque size. All of our patients suffered from inability to intercourse due to significant penile curvature but after the procedure 11 of them (66.1%) could do so. Also the BSFI score improved significantly in this subgroup (P < 0.05). The remaining 7 cases (39%) already suffered from erectile dysfunction despite of operation; however, the penile curvature improved significantly in them. Six of this latter group had a plaque size greater than 4 cm2 and BSFI score was not significantly improved. Conclusion: Dermal patch graft as a cost effective method in the management of Peyronie’s disease significantly corrects the curvature irrespective of plaque size and curvature severity. We found that if the fibrous plaque is less than 4 cm2 and the patient has no severe erectile dysfunction, this procedure will significantly improve his potency; however, if the patient suffers from a plaque sized greater than 4 cm2 and/or severe erectile dysfunction, to reach satisfactory erection, implantation of penile prosthesis or applying other methods of artificial erection in addition to dermal patch graft is suggested.